2013
DOI: 10.1149/05301.0251ecst
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Deep Levels Associated with Extended and Point Defects in GeSn Epitaxial Layers Using DLTs

Abstract: Deep levels associated with extended and point defects in MOS capacitors fabricated on unintentionally doped GeSn epitaxial layers on Ge-on-Si substrates have been studied by Deep Level Transient Spectroscopy (DLTS). A 9nm layer of Al2O3 is deposited as high-k gate dielectric by Molecular Beam Epitaxy. The trap kinetics and origin of defect states is discussed. Also, it is shown that the dislocation cores in relaxed p-Ge are associated with band-like donor-like states in the lower half of forbidden band gap, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The H1 and H2 peaks at 130 and 160 K, respectively, visualized by using deconvoluted spectra (green lines) are due to bulk traps in the Ge buffer. 21 The peak response at 250 K is due to slow states (N bt ) and is not discussed in this work. The inset shows the shift in peak position as a function of period width T w .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The H1 and H2 peaks at 130 and 160 K, respectively, visualized by using deconvoluted spectra (green lines) are due to bulk traps in the Ge buffer. 21 The peak response at 250 K is due to slow states (N bt ) and is not discussed in this work. The inset shows the shift in peak position as a function of period width T w .…”
mentioning
confidence: 99%
“…The peak at 70K is due to D it . The H1 and H2 peaks at 130 and 160 K, respectively, visualized by using deconvoluted spectra (green lines) are due to bulk traps in the Ge buffer . The peak response at 250 K is due to slow states ( N bt ) and is not discussed in this work.…”
mentioning
confidence: 99%
“…17 Moreover, it has been reported that defects around the midgap (E V +0.29 eV) in Ge 1−x Sn x /Ge epitaxial layers appear to be associated with threading dislocations. 18 The physical origin and bez E-mail: wtakeuti@alice.xtal.nagoya-u.ac.jp havior of these hole-generating defects holes have not been clarified. One possible origin of the hole-generating defects is related to multivacancy complexes in the Ge matrix, which are known as acceptor-like states with an energy level of 10-20 meV above the valence band.…”
mentioning
confidence: 99%
“…A similar behavior, in which the buffer actively participates in the strain relaxation mechanism, has already been noticed for GeSn binaries grown at low temperatures on Ge‐VS in the same reactor . The absence of extended defects in the SiGeSn layer, such as threading dislocations or stacking faults, is especially beneficial for opto‐ and nanoelectronic applications, since, e.g., threading dislocations are known to form midgap trap states, thus seriously influencing device performance.…”
Section: Resultsmentioning
confidence: 83%